Hippocampal subfield microstructure abnormalities mediate associations between tau burden and memory performance: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Nir, Talia M; Salminen, Lauren; Reina, Julio E Villalon; Tubi, Meral A; Thomopoulos, Sophia I; Maiti, Piyush; Braskie, Meredith N; Thompson, Paul M; Jahanshad, Neda
Abstract: Background: Alzheimer's disease (AD) pathology in the medial temporal lobes, including tau accumulation, is associated with memory impairment. This relationship may be mediated by microstructural changes in hippocampal tissue, particularly in subregions with prominent tau deposition and neuronal loss such as the CA1 and subiculum. Multi‐shell diffusion MRI (dMRI) can be used to fit biophysical models, such as Neurite Orientation Dispersion and Density Imaging (NODDI), which estimate intracellular (ICVF) and CSF (ISOVF) volume fractions in brain microstructure; these measures may offer enhanced specificity and sensitivity to disease processes such as neuronal loss and inflammation. Here, we evaluated the relationships between hippocampal subfield PET tau accumulation (F‐AV1451), NODDI microstructure, and a composite measure of memory performance (ADNI‐Mem) in the ADNI‐3 database. Methods: Data were available for 70 ADNI‐3 participants (age: 73.6±6.7yrs; 40F; 48 CN, 18 MCI, 4 with dementia). NODDI measures (ICVF, ISOVF) were estimated using a novel multi‐tissue approach (MT‐NODDI); a gray matter specific response function was used to improve estimates in the hippocampus. Hippocampal subfields were parcellated from T1w images using FreeSurfer, and mean dMRI‐NODDI and PET‐AV1451 measures were extracted from 11 individual subfields and 9 composite subregions (Fig 1a). For each ROI, linear regressions tested associations between (1) MT‐NODDIROI and TauROI, (2) ADNI‐Mem and TauROI, and (3) ADNI‐Mem and TauROI while adjusting for MT‐NODDIROI (Fig 1b). We used FDR ( q =0.05) to adjust for multiple tests. Mediation analyses were performed for regions showing significant associations in models 1 and 2. Results: Higher regional tau was associated with lower ADNI‐Mem (Fig 2a). Higher tau depositions were also associated with lower ICVF and higher ISOVF (Fig 2b); MT‐NODDI measures detected significant associations with tau where standard NODDI did not (Fig 3). Excluding subfields comprising the subiculum‐complex, the negative effects of tau on memory scores were mediated by lower ICVF and higher ISOVF (Fig 4). Conclusions: Tau pathology may lead to memory deficits through a variety of mechanisms, including hippocampal microstructural changes such as neuronal loss or increased inflammatory processes (lower ICVF and increased ISOVF) in subfields downstream from the subiculum‐complex.